2020
DOI: 10.1002/ajmg.a.61810
|View full text |Cite
|
Sign up to set email alerts
|

Tuberous sclerosis complex (TSC), lymphangioleiomyomatosis, and COVID‐19: The experience of a TSC clinic in Italy

Abstract: Individuals with comorbidities are at higher risk of coronavirus disease 2019 (COVID-19) and worse outcome, but little information has been available about patients with genetic diseases and COVID-19. This study aims at evaluating the presence and outcome of COVID-19 in a cohort of Italian patients with tuberous sclerosis complex (TSC) and/or lymphangioleiomyomatosis (LAM), and at reviewing the possible effects of mTOR inhibitors on SARS-CoV-2 infection. We included 102 unselected individuals with a diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“… 130 In agreement with this hypothesis, hospitalized patients with critical COVID-19 treated with NAC showed significant clinical improvement and reduction of inflammation markers, suggesting a beneficial effect of NAC in COVID-19, possibly mediated by mTOR inhibition. 131 Limited observational studies of patients with tuberous sclerosis complex (TSC) and/or lymphangioleiomyomatosis (LAM) on long-term mTOR inhibitors (sirolimus or everolimus) have not identified an increased risk of COVID-19 or poor outcomes of the infection 132 , 133 and clinical trials of mTOR inhibitors in COVID-19 are ongoing. However, whether activation of the mTOR pathway plays a role in SARS-CoV-2-infected patients with SLE remains to be elucidated.…”
Section: Convergent Immunopathogenic Mechanisms Of Covid-19 and Slementioning
confidence: 99%
“… 130 In agreement with this hypothesis, hospitalized patients with critical COVID-19 treated with NAC showed significant clinical improvement and reduction of inflammation markers, suggesting a beneficial effect of NAC in COVID-19, possibly mediated by mTOR inhibition. 131 Limited observational studies of patients with tuberous sclerosis complex (TSC) and/or lymphangioleiomyomatosis (LAM) on long-term mTOR inhibitors (sirolimus or everolimus) have not identified an increased risk of COVID-19 or poor outcomes of the infection 132 , 133 and clinical trials of mTOR inhibitors in COVID-19 are ongoing. However, whether activation of the mTOR pathway plays a role in SARS-CoV-2-infected patients with SLE remains to be elucidated.…”
Section: Convergent Immunopathogenic Mechanisms Of Covid-19 and Slementioning
confidence: 99%
“…Similarly, some patients could have been asymptomatic at the time of the study but were unaccounted for due to limited RT-PCR testing. As such, these patients may still have a higher risk of COVID-19 infection (Peron et al, 2020). (Ramos, Pilewski, Faro, & Marshall, 2020).…”
Section: Although Previous Experience During the H1n1 Pandemic In 2009mentioning
confidence: 99%
“…We read with great interest the article entitled "Tuberous sclerosis complex (TSC), lymphangioleiomyomatosis, and COVID-19: The experience of a TSC clinic in Italy" by Peron et al (2020), which described the features and outcomes of coronavirus in patients with tuberous sclerosis complex (TSC) and lymphangioleiomyomatosis (LAM) in Italy, and the potential role of mTOR inhibitors in such infection. Here, we present our experience of patients with LAM and COVID-19, with an emphasis on the potential influence of the use of mTOR inhibitors.…”
mentioning
confidence: 99%
“…investigate the occurrence of COVID-19 specifically in a sample of patients with LAM. Peron et al suggested that TSC and LAM patients do not have an increased risk of developing COVID-19 and discussed the potential risks and benefits of maintaining the use of mTOR inhibitors regarding such infection(Peron et al, 2020). A relevant limitation raised by the authors was the lack of confirmation of the COVID-19 diagnosis by PCR in most of the patients(Peron et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation